INSTITUTIONAL BARRIERS TO EMPLOYMENT IN THE HEALTHCARE SECTOR: REGULATIONS AND THEIR IMPACT - Kilasonia, Nikoloz (Social Economics, 2025)
The healthcare sector is critically important for a country’s socio-economic stability, as public health directly influences not only the overall quality of life but also workforce productivity and national economic growth. A well-functioning healthcare system ensures a healthier population, leading to a more effective labor force and increased economic output. However, despite its significance, the employment process in Georgia’s healthcare system faces numerous institutional barriers that limit the sector’s ability to attract, integrate, and retain skilled professionals. These barriers not only restrict job opportunities for newly trained medical personnel but also negatively impact the accessibility and quality of medical services across the country. This study comprehensively examines the key institutional obstacles within the Georgian healthcare labor market. It identifies the primary challenges, including low wages that demotivate medical professionals, a significant mismatch between education and employment due to a lack of structured career guidance, insufficient digitalization within the sector that hampers efficiency, an acute shortage of nursing staff that affects service quality, and the absence of a long-term strategic vision for workforce planning and healthcare modernization. These factors collectively contribute to labor market inefficiencies, high turnover rates, and an imbalanced distribution of healthcare professionals, particularly between urban and rural areas, exacerbating regional disparities in medical service provision. The research methodology is based on a mixed-method approach, incorporating both quantitative and qualitative research techniques to provide a thorough assessment of the issue. Quantitative research was conducted through structured surveys. These surveys assessed key employment-related challenges, regulatory barriers, and workforce expectations. Qualitative research was carried out through in-depth interviews with industry professionals to gain deeper insights into systemic inefficiencies and potential policy interventions. Based on the research findings, this study proposes several policy recommendations aimed at improving employment conditions within the healthcare sector. These include revising the salary system and implementing financial incentives to increase workforce retention, developing career mentoring programs to better align medical education with labor market demands, accelerating the digital transformation of healthcare services to enhance efficiency, actively promoting the nursing profession through training programs and better compensation structures, and formulating a long-term employment strategy that integrates technological advancements and systematic workforce planning. Addressing these institutional barriers is crucial for modernizing Georgia’s healthcare system, ensuring the long-term sustainability of the sector, and improving the overall quality of medical services. Implementing the proposed reforms would not only enhance job satisfaction and professional growth opportunities for healthcare workers but also contribute to better public health outcomes and a more resilient healthcare infrastructure.